RI Photometry of 32 Cygni - Jang Hae Jeong; Yonggi Kim; Il-Seong Nha (Journal of Astronomy and Space Sciences, 1992)
Surface activity of the late-type supergiant component of ζ Aurtype eclipsing binary 32 Cyg has been searched in R and I passbands for 53 nights in the 1991 season. Atmospheric extinctions in these wavelength regions are made and a linear relation between the two coefficients has been found. All the data are standardized and determined the magnitudes and colors of 32 Cyg. R, I and color curves of 32 Cyg at the outside eclipse phase are presented.